2008
DOI: 10.2139/ssrn.1275395
|View full text |Cite
|
Sign up to set email alerts
|

Fair Value Accounting and Financial Stability

Abstract: Market prices give timely signals that can aid decision making. However, in the presence of distorted incentives and illiquid markets, there are other less benign effects that inject artifi cial volatility to prices that distorts real decisions. In a world of marking-to-market, asset price changes show up immediately on the balance sheets of fi nancial intermediaries and elicit responses from them. Banks and other intermediaries have always responded to changes in economic environment, but marking-to-market sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 3 publications
0
37
0
5
Order By: Relevance
“…There are essentially two arguments why FVA can contribute to procyclicality: one in booms and one in busts. 8 The first argument is that FVA and asset write-ups allow banks to increase their leverage in booms, which in turn makes the financial system more vulnerable and financial crises more severe (e.g., Persaud, 2008;Plantin et al, 2008b). 9 In contrast, HCA prohibits asset write-ups in booms and creates "hidden" reserves, which can be drawn upon in times of crisis.…”
Section: Fair-value Accounting Illiquidity and Financial Crisesmentioning
confidence: 99%
“…There are essentially two arguments why FVA can contribute to procyclicality: one in booms and one in busts. 8 The first argument is that FVA and asset write-ups allow banks to increase their leverage in booms, which in turn makes the financial system more vulnerable and financial crises more severe (e.g., Persaud, 2008;Plantin et al, 2008b). 9 In contrast, HCA prohibits asset write-ups in booms and creates "hidden" reserves, which can be drawn upon in times of crisis.…”
Section: Fair-value Accounting Illiquidity and Financial Crisesmentioning
confidence: 99%
“…16 Thus, the fair-value accounting method leads to an endogenous volatility of prices (Platin et al, 2008a;2008b), making procyclicality endogenous. Moreover, the volatility caused by this method may increase because of estimation errors, inherent volatility and the use of the mixed attributes model (i.e., the application of fair-value accounting to some instruments and amortized cost accounting to others) when preparing financial statements, thus reducing the net effect (Barth, 2004).…”
Section: Potential Drawbacks Of Current Accounting Standardsmentioning
confidence: 99%
“…Plantin et.al. [14] considered that under fair value accounting, asset write-ups allow banks to increase leverage in period of economic expansion, which make the financial system more vulnerable and bring volatility and contagion to financial market. Adrian and Shin [15] used the sampling data of American financial institutions and found that financial institutions using fair value could suffer pro-cyclical effects, which may bring more risks to banking and capital market.…”
Section: Fair Value Accountingmentioning
confidence: 99%
“…Under fair value accounting, the value of asset is allowed to be written up and written down; as such, when the market is preposterous, the market value of asset tends to increase. Asset write-ups enable companies to increase leverage, which introduces high risks to corporate finance [2]. However, when it comes to macroeconomic depression, fair value write-downs magnify losses and cause panic among investors.…”
Section: Introductionmentioning
confidence: 99%